Nursing: a study of the physiopathology of Alzheimer’s and its alternative treatments with stem cells and cannabis (Research, Society and Development, 2020)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterized by the loss of synapses, brain neurons and deposits of fibrils of beta-amyloid-extraneuronal peptides, constituting the senile plaques, forming neurofibrillary tangles. With the growth of the elderly population mainly in Brazil, studies point out the public health concern regarding the growth of AD cases and the future of their treatment. The general objective is to analyze the aspects related to alternative treatments aimed at AD, the specific ones describe the treatments with stem cells (cell therapy), the use of Cannabidiol and herbal medicines and the discussion about the applicability of treatments alternatives to AD (Alzheimer's disease). Through studies conducted with the use of Cannabis substance and cell therapy (stem cells) that have generated positive results, scientists recommend caution, as the complexity of AD still requires years of research.